2012
DOI: 10.1155/2012/604098
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Constrictive Pericarditis in a Holstein Heifer

Abstract: The field diagnosis of constrictive pericardial effusion is often established on the pertinent pathognomonic physical examination findings, but the condition cannot be ruled out based on absence of these cardinal signs. Constrictive pericardial effusion is not always manifested by bilateral jugular venous distention and pulsation, brisket edema, and muffled heart sounds, all of which are considered the key points in the field diagnosis of pericardial effusion and hardware disease. This case will also document … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…(2010) [14] who recorded 17.06% incidence in slaughtered cattle in Zaria abattoir. Macroscopic findings such as pericardium showed thickening and epicardium showed granulation tissue agreed well with the earlier findings recorded by Chanie and Tesfaye (2012) [7] , Elhanafy and French (2012) [8] . The microscopic findings of pericarditis such as fibrin sediments and marked infiltration of polymorphonuclear cells along with diffuse congestion in accordance with the findings of Bastianello and Stella (1981) [2] , Chanie and Tesfaye (2012) [7] , Ghanem, (2010) [9] , Vujanac et al (2013) [15] and Hussein and Staufenbiel (2014) [11] .…”
Section: Discussionsupporting
confidence: 91%
“…(2010) [14] who recorded 17.06% incidence in slaughtered cattle in Zaria abattoir. Macroscopic findings such as pericardium showed thickening and epicardium showed granulation tissue agreed well with the earlier findings recorded by Chanie and Tesfaye (2012) [7] , Elhanafy and French (2012) [8] . The microscopic findings of pericarditis such as fibrin sediments and marked infiltration of polymorphonuclear cells along with diffuse congestion in accordance with the findings of Bastianello and Stella (1981) [2] , Chanie and Tesfaye (2012) [7] , Ghanem, (2010) [9] , Vujanac et al (2013) [15] and Hussein and Staufenbiel (2014) [11] .…”
Section: Discussionsupporting
confidence: 91%
“…The hearts were covered with yellow fibrin shreds with fibrinous adhesions. The same gross lesions were observed by (Elhanafy and French, 2012).They found that the pericardial sac was totally lined by a large mat of thick yellow fibrinous material. Fibrous adhesions also found at necropsy in all cases in animals with fatal traumatic pericarditis (Roth and King, 1991).…”
Section: Discussionsupporting
confidence: 67%
“…Ultrasonographic examinations of lungs revealed pleural effusions (3 buffaloes), lung consolidation (12 buffaloes), and lung abscess (1 buffalo). These findings may be due to disseminated infections from pericarditis or endocarditis (7,28). Results in the present study suggest that the prognosis of congestive cardiac failure in buffaloes as a result of traumatic pericarditis or endocarditis is poor, but from the economic point of view for pregnant ones, it may be helpful to immobilize the diseased animals with therapeutic trials until calving; however, deterioration of their health condition could still develop later on.…”
Section: Discussionmentioning
confidence: 67%
“…These alterations could be considered a complication related to traumatic reticuloperitonitis (28). Perireticular abscesses were recognized as round or oval echogenic structures with homogeneous or heterogeneous contents and a distinct hyperechogenic capsule, which was confirmed at necropsy examination.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation